Decolonizing Diets: Idol Food, Jewish Diaspora, and the Crisis of John’s Apocalypse - Mata, Roberto (Biblical interpretation, 2024)
This article explores how Revelation’s Jewish Diaspora negotiated the Roman colonial situation of Asia Minor through their stance on idol food. Scholars have suggested that John wrote to Christians suffering imperial persecution under Domitian. Still, others have proposed a perceived crisis, a prophetic rivalry relating to Greco-Roman society, or a summons to a holy war. However, some of these mostly depoliticizing trends presuppose the so-called partying of the ways and neglect to explore the centrality of ritual food and its association with Roman imperial authority. Drawing on Frantz Fanon’s analysis of colonial situations and sociological notions of food and eating, I map how John and the inscribed Jewish Diaspora communities of Revelation turned idol food into a locus for negotiating Roman colonial authority in Asia Minor circa 100 C.E.